Fragility of epidermis and its consequence in dermatology. (June 2014) - Stalder, J.F.; Tennstedt, D.; Deleuran, M.; Fabbrocini, G.; de Lucas, R.; Haftek, M.; Taieb, C.; Coustou, D.; Mandeau, A.; Fabre, B.; Hernandez‐Pigeon, H.; Aries, M.F.; et al.
Abstract: The skin is the largest organ of the body, providing a protective barrier against bacteria, chemicals and physical insults while maintaining homeostasis in the internal environment. Such a barrier function the skin ensures protection against excessive water loss. The skin's immune defence consists of several facets, including immediate, non‐specific mechanisms (innate immunity) and delayed, stimulus‐specific responses (adaptive immunity), which contribute to fending off a wide range of potentially invasive microorganisms. This article is an overview of all known data about 'fragile skin'. Fragile skin is defined as skin with lower resistance to aggressions. Fragile skin can be classified into four categories up to its origin: physiological fragile skin (age, location), pathological fragile skin (acute and chronic), circumstantial fragile skin (due to environmental extrinsic factors or intrinsic factors such as stress) and iatrogenic fragile skin. This article includes the epidemiologic data, pathologic description of fragile skin with pathophysiological bases (mechanical and immunological role of skin barrier) and clinical description of fragile skin in atopic dermatitis, in acne, in rosacea, in psoriasis, in contact dermatitis and other dermatologic pathologies. This article includes also clinical cases and differential diagnosis of fragile skin (reactive skin) in face in adult population. In conclusion, fragile skin is very frequent worldwide and its prevalence varies between 25% and 52% in Caucasian, African and Asian population.